THU0152 Incidence of Opportunistic Infections in Rheumatoid Arthritis Treated with Biological Agents. (10th June 2014) - Gόmez, A.; Rosales Rosado, Z.; Peña, R.; Toledano, M.E.; Arietti, L.; Pato, E.; Leόn, L.; Blanco, M.; Jover, J.Ά.; Rodríguez, L.; Abásolo, L.
Abstract : Background: With the expanding use of Biological Agents (BA), in particular TNF inhibitors, opportunistic infections (OI) are a major concern in Rheumatology. Objectives: a) To describe the incidence of OI global and by periods in Rheumatoid Arthritis (RA). b) To compare the risk of OI by BA. Methods: We performed a retrospective longitudinal observational study from 1/1/2000 to 23/11/2013. We included subjects followed up in our outpatient clinic, diagnosed with RA according to ACR criteria 87, whom started treatment with a BA [etanercept (ETN), golimumab (GOLI), certolizumab (CTZ), infliximab (IFX), adalimumab (ADA), rituximab (RTX), abatacept (ABA), or tozilizumab (TZL)]. Our primary end point was OI that involved the suspension of the BA. We consider OI when there was a positive culture (for Candida, Aspergillus or Herpes) or compatible symptoms that responded to specific treatment. We also collected secondary variables: sociodemographic (age, sex); clinical (disease duration, types of BA, hospital admission, previous BA). Statistical analysis: We used survival techniques to estimate the incidence of global OI and OI by periods (1st: 98-2002, 2nd:2002-2007, 3rd: 2007-2013), expressed per 1000 patient-year [CI 95%]. The exposure time was defined from the start date of each BA to suspension, loss of follow up or end of study (23/11/2013). We performed Cox regression models (adjusted by age, duration of RA, sex, calendar time and prior BA) to compare the risk of OI between each BA. Results: 405 RA patients were included in the study, they started 744 different courses of BA treatment, with a total follow-up of 1, 612 patient-years. Of these, 81% were women with a mean age at diagnosis of 52.5±13 years. The most frequently used drug was ADA (32%), followed by ETN (25%), IFX (21%) and RTX (14%). There were 16 OI (6 Candidas, 2 Aspergillus and 8 Herpes Zoster), 40% required hospitalization and two died of disseminated candidiasis. The incidence of OI was 9.9 [6.1-16.2], and tended to increase over time (1st: 5.9 [1.5 to 23.9]; 2nd: 7.7 [2.9 to 20, 6]; and 3rd: 13.1 [7.1 to 24.3]). We only registered OI cases in anti-TNF and RTX, which is the drug with higher incidence (n=3, I: 20.1 [6.4 to 62.4]). We found no statistically significant association between RTX compared with other BA and the development of OI Conclusions: The incidence of OI and its evolution over time in real life conditions is described. It seems that OI tend to increase over time and we had two cases with fatal outcome. Doctors using BA should be concerned about this problem and be aware of the optimal methods for the detection and management of OI. We did not find statistical differences in the rate of OI between BA. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4509